TERAPI ANTIBIOTIK UNTUK TRAVELLER’S DIARRHEA DI ASIA TENGGARA : TINJAUAN GLOBAL TERKINI DAN TANTANGAN RESISTENSI MIKROBA: Antibiotic Therapy for Traveler’s Diarrhea in Southeast Asia: Current Global Review and Challenges of Microbial Resistance - I Made Wiracana; Wahyuni W.Udi (Journal Pharmactive, 2025)
Traveler’s diarrhea (TD) is defined as the passage of three or more loose stools within a 24-hour period occurring during or shortly after travel. Southeast Asia is classified as a high-risk region, with an incidence rate of TD of at least 20%. The majority of TD cases are caused by bacterial pathogens, particularly Escherichia coli. In Southeast Asia, other organisms, including Campylobacter, are also frequently implicated. Although multiple clinical guidelines recommend antibiotic therapy for TD, antimicrobial resistance has emerged as a major challenge in its management. Despite available prevention and treatment guidelines, the development of antibiotic resistance in Southeast Asia after 2019 has not been adequately addressed in previous reviews. This narrative review aims to fill the gap identified in Hitch’s (2019) review by evaluating antibiotic therapy patterns for TD in the Southeast Asian context, with a specific focus on microbial resistance. The study employed a narrative review approach based on the PRISMA-P 2015 guidelines. Six studies or review articles addressing antibiotic resistance patterns among TD-related pathogens in Southeast Asia were included. The findings demonstrate substantial resistance of Campylobacter to fluoroquinolone antibiotics. Azithromycin remains the recommended therapy for moderate to severe TD; however, ciprofloxacin prescribing for TD is still reported in the Bali region.